Testing of resistance to downy mildew on several sweet corn inbred lines of 7th generation - Kustanto, Heri (Kultivasi, 2023)
Sweet corn is one of the most well-known horticultural crop commodities and can adapt to various climates and environments. Efforts to control downy mildew disease continue to be carried out in collaboration with various parties in different ways, including genetic improvement of the varieties planted. The purpose of this study was to test the resistance of the 7th generation of sweet corn inbred lines to downy mildew and to find out the phenotypic characters that affect downy mildew. The new inbred lines obtained from the results of a long breeding process will be better tested for resistance to downy mildew before crosses are carried out among these inbred lines to guarantee better the development of new varieties of sweet corn that are resistant to downy mildew. The experiment was conducted from August to November 2019 in Getasrejo, Grobogan, and Central Java. The material consisted of 10 kinds of maize inbred line seeds and two comparison varieties. The experiment was carried out using a randomized block design with three replications. One of the obstacles that is difficult to overcome in sweet corn cultivation is downy mildew disease (Peronosclerospora spp.). The conclusions of this study were: (1) Inbred lines HSJM 08, HSJM 06, HSJM 07, HSJM 02, HSJM 05, HSJM 04, and HSJM 01 were categorized as highly resistant genotypes. HSJM 09 can be categorized as a resistant inbred line. Inbred lines HSJM 10 and HSJM 03 were classified as moderately resistant genotypes. (2) The characters of leaf width, leaf length, leaf wet weight, leaf dry weight, and leaf moisture content can be considered in determining selection criteria against downy mildew disease on sweet corn.Keywords: attack, resistance, sweet corn, downy mildew